What is the comparative effectiveness of cognitive behavioral therapy versus medical treatment in improving sexual function for women with sexual dysfunction? - Yunike Putri Nurfauzia; I Made Adi Saputra Wijaya; Mutia Juliana; Yahya Nurlianto (The International Journal of Medical Science and Health Research, 2025)
Introduction: This review investigates the comparative effectiveness of Cognitive Behavioral Therapy (CBT) versus medical treatments in improving sexual function among adult women diagnosed with sexual dysfunction. Sexual dysfunctions studied include provoked vestibulodynia (PVD), hypoactive sexual desire disorder (HSDD), vaginismus, and related conditions. Methods: Fifteen studies, primarily randomized clinical trials, were analyzed. Interventions included various forms of CBT (couple-based, group-based, mindfulness-based) and medical treatments such as lidocaine, sildenafil, bupropion, and topical steroids. Outcomes measured were sexual function, pain, sexual satisfaction, psychological distress, and relational factors. Results: CBT consistently showed significant improvements in sexual function, psychological well-being, and relationship satisfaction. For example, one study reported a 66% improvement in sexual performance after 12 weeks of CBT, and another showed an 18-point increase in sexual function scores at six months follow-up. Medical treatments provided rapid relief of physiological symptoms like pain and lubrication deficits, with effect sizes sometimes comparable to CBT. However, CBT was more effective in addressing psychological and relational aspects. Discussion: CBT’s holistic approach addresses both physiological and psychological factors, offering longer-lasting benefits and skill development for patients. Medical treatments are advantageous for quick symptom relief and ease of administration. Combined approaches may optimize outcomes. Conclusion: Both CBT and medical treatments are effective, but CBT offers broader and potentially more durable improvements in sexual health. Treatment choice should be individualized based on patient needs and dysfunction type.